ASPM and CITK regulate spindle orientation by affecting the dynamics of astral microtubules. (2nd October 2017) - Gai, Marta; Bianchi, Federico T; Vagnoni, Cristiana; Vernì, Fiammetta; Bonaccorsi, Silvia; Pasquero, Selina; Berto, Gaia E; Sgrò, Francesco; Chiotto, Alessandra A; Annaratone, Laura; Sapino, Anna; Bergo, Anna; et al.
Abstract :